An Overview on Nanocrystalline ZnFe2O4, MnFe2O4, and CoFe2O4 Synthesized by a Thermal Treatment Method. (4th July 2012) - Goodarz Naseri, Mahmoud; Saion, Elias B.; Kamali, Ahmad
Abstract : This study reports the simple synthesis of MFe2 O4 (whereM = Zn, Mn, and Co) nanoparticles by a thermal treatment method, followed by calcination at various temperatures from 723 to 873 K. Poly(vinyl pyrrolidone) (PVP) was used as a capping agent to stabilize the particles and prevent them from agglomeration. The characterization studies were conducted by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The average particle sizes were obtained by TEM images, which were in good agreement with the XRD results. Fourier transform infrared spectroscopy (FT-IR) confirmed the presence of metal oxide bands for all the calcined samples. Magnetic properties were demonstrated by a vibrating sample magnetometer (VSM), which displayed that the calcined samples exhibited superparamagnetic and ferromagnetic behaviors.